Non-pharmacological methods of labor pain relief - Michalczyk, Michał; Torbé, Dorota; Torbé, Andrzej (Journal of Education, Health and Sport, 2018)
Birth of a child is an unique time in the life of every woman. Unfortunately, labor is often one of the most painful and traumatic experiences suffered in her life. In the modern obstetrics pain of labor and methods of its mitigation are the main problem for both, patients and medical staff. In this paper non-pharmacological methods of labor pain relief, including hypnosis, biofeedback, water immersion, aromatherapy, relaxation techniques, acupuncture, massage, reflexology and transcutaneous electrical nerve stimulation were described.